(untitled) (Research, Society and Development, 2021)
Social isolation has been an important measure to contain the pandemic caused by COVID-19. Given this context, schools had to suspend classes and consequently and the National School Meals Program (PNAE) suffered a major impact, generating many challenges to continue the program within a pandemic scenario. Several regulations were regulated to reduce the impacts issued, such as the authorization of the distribution of foodstuffs acquired under the PNAE to those responsible for students during the pandemic. A very affected sector was family farming, whose PNAE is the main consumer of its products. With classes suspended, the situation became very complex. The purpose of this study is to discuss the challenges for implementing the PNAE in relation to the purchase of family farming during a pandemic by Covid-19. A bibliographic search was carried out based on documentary and bibliographic sources, from March 2020 to February 2021, referring to PNAE and family farming. The Covid-19 pandemic brought new challenges, which must be discussed and overcome, through actions that guarantee support to farmers, with the aim of reducing the effects of the pandemic.